2018
DOI: 10.3390/molecules23113039
|View full text |Cite
|
Sign up to set email alerts
|

Coptisine Suppresses Mast Cell Degranulation and Ovalbumin-Induced Allergic Rhinitis

Abstract: Coptisine is one of the main components of isoquinoline alkaloids in the coptidis rhizome. The effect of coptisine on allergic rhinitis has not been investigated. In this study, we report the effects and mechanisms of coptisine using monoclonal anti-2,4,6-dinitrophenyl-immunoglobulin (Ig) E/human serum albumin (DNP-IgE/HSA)-stimulated rat basophilic leukemia cells (RBL-2H3 cells) in vitro and an ovalbumin (OVA)-induced allergic rhinitis (AR) in mice. The results showed that coptisine markedly decreased the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…Membrane structure changes in activated mast cells have been shown to follow the cross‐linking of cell surface receptors by external antigens (Briggs, 1963), the redistribution of actin filaments (Deng et al, 2009), and decoupling of the cytoskeleton from the plasma membrane ( Draber et al, 2012). The inhibition of mast cell activation by tozasertib in vitro appeared to be similar to that induced by coptisine, a cytotoxic alkaloid used in traditional Chinese medicine, shown to prevent granule release and F‐actin reorganization (Fu et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Membrane structure changes in activated mast cells have been shown to follow the cross‐linking of cell surface receptors by external antigens (Briggs, 1963), the redistribution of actin filaments (Deng et al, 2009), and decoupling of the cytoskeleton from the plasma membrane ( Draber et al, 2012). The inhibition of mast cell activation by tozasertib in vitro appeared to be similar to that induced by coptisine, a cytotoxic alkaloid used in traditional Chinese medicine, shown to prevent granule release and F‐actin reorganization (Fu et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…The mixture was discarded, and the fixed cells were stained with 300 μl of toluidine blue dye (1% w/v in 0.9% NaCl solution, pH 2.5) for 30 min. Images of the stained cells were examined for heterochromatin particles with an inverted microscope (Carl Zeiss, Goettingen, Germany; Fu, Ni, Wang, & Hong, 2018; Kruger & Bloom, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that coptisine (1‐30 μmol/L, 15 minutes‐24 hours) inhibited LPS‐induced inflammatory response in Raw 264.7 macrophages which was attributed by coptisine‐mediated blocking of NF‐κB, MAPK and PI3K/AKT pathway signalling transduction . Coptisine (10‐30 μmol/L, 12 hours) was also reported to decrease productions of histamine, IL‐4 and TNF‐α in (DNP‐IgE/HSA)‐stimulated rat RBL‐2H3 cells by suppressing PI3K/Akt phosphorylation . The findings of Zhou et al demonstrated that coptisine treatment reversed IL‐1β‐induced p‐p65 mRNA/protein overexpression and IκBα degradation in OA chondrocyte .…”
Section: Anti‐inflammation Propertymentioning
confidence: 96%
“…Similarly, inhibition of inflammatory process was also observed in animal models including xylene‐induced ear oedema, carrageenan‐elicited paw oedema, LPS‐induced shock, OVA‐induced allergic rhinitis and MSU‐elicited gouty after coptisine administration . Mechanistically, coptisine (50‐200 mg/kg, oral, once daily for 10 days; 10‐40 mg/kg, oral, once daily for 7 days; 2.91‐11.61 mg/kg, i.v, single dose, 0‐24 hours) diminished cytokine production through blocking inflammatory transduction mediated by the phosphorylation of IKKα/β and MAPK subfamilies, the translocation and degradation of p65 in oedema tissue as well as suppression of NLRP3 inflammasome activation . Of interest, coptisine (0.97‐3.87 mg/kg, i.v; single dose, 0‐4 hours) showed no effect on the up‐regulation of oedema skin temperature induced by carrageenan subcutaneously injection in rats .…”
Section: Anti‐inflammation Propertymentioning
confidence: 99%
See 1 more Smart Citation